2022
DOI: 10.3390/antibiotics11050663
|View full text |Cite
|
Sign up to set email alerts
|

Direct Urine Resistance Detection Using VITEK 2

Abstract: Urinary tract infections (UTIs) are the most common infectious diseases in both communities and hospitals. With non-anatomical or functional abnormalities, UTIs are usually self-limiting, though women suffer more reinfections throughout their lives. Certainly, antibiotic treatment leads to a more rapid resolution of symptoms, but also it selects resistant uropathogens and adversely affects the gut and vaginal microbiota. As uropathogens are increasingly becoming resistant to currently available antibiotics, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The method of Vitek-2 is regarded as an automatic identification system for microorganisms to show the phenotype of the isolates tested and able to determine the sensitivity or resistance of an isolate to antibiotics [24].…”
Section: Discussionmentioning
confidence: 99%
“…The method of Vitek-2 is regarded as an automatic identification system for microorganisms to show the phenotype of the isolates tested and able to determine the sensitivity or resistance of an isolate to antibiotics [24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported the use of FCM for the selection of positive urine specimens, followed by bacterial identification with MALDI-TOF MS and then direct testing AST with the VITEK 2 system to reduce the waiting time for results by up to one day [ 54 , 64 ]. In addition, FCM combined with DiBAC4(3), a membrane potential-sensitive dye, enabled direct AST in urine samples [ 37 ].…”
Section: Rapid Detection Of Bacterial Pathogens and Resistance–contri...mentioning
confidence: 99%
“…The FCM instrumental platforms could be included in such integrated trans-sectorial surveillance programs as they can increase the surveillance throughput and decrease the time to results. Currently, FCM-based methodologies have already demonstrated their ability to detect antibiotic resistance bacteria in human and animal biological samples [ 54 , 62 , 64 , 98 ], and in environmental samples [ 88 , 99 , 100 ]. Williams et al (2017) [ 101 ] introduced an approach based on FCM for the detection and counting of E. coli O157:H7 pathogen directly in food (raw spinach) that proved more sensitive than the reference method.…”
Section: Perspectives For Further Contributions Of Fcm In Tackling Amrmentioning
confidence: 99%
“…Technically, for a patient presenting symptoms of a urinary tract infection, any microbial concentration in the test results may indicate an infection. However, in order to be clinically diagnosed as a UTI, the microbial load should surpass a threshold of 10 5 colony-forming units per milliliter (CFU/mL) of urine [10]. In the realm of urinary tract infection detection, the gold standard diagnostic method involves the collection of urine samples, followed by a subsequent culture [11].…”
Section: Introductionmentioning
confidence: 99%